Prevalence of dyslipidaemia among adults in Africa: a systematic review and meta-analysis - Jean Jacques Noubiap, MD; Jean Joel Bigna, MD; Jobert Richie Nansseu, MD; Ulrich Flore Nyaga, MD; Eric Vounsia Balti, MD; Justin B Echouffo-Tcheugui, MD; André Pascal Kengne, MD (Elsevier, 2018)
Summary: Background: The burden of dyslipidaemia in Africa remains inadequately characterised. We aimed to estimate the prevalence of dyslipidaemia in African adults from hospital-based and community-based studies. Methods: In this systematic review and meta-analysis, we searched MEDLINE via PubMed, Embase, African Journals Online, and African Index Medicus for studies published between Jan 1, 1980, and July 31, 2017, without language restriction. We assessed methodological quality of all cross-sectional studies reporting on the prevalence of elevated concentrations of total cholesterol, LDL cholesterol, or triglycerides, or low concentrations of HDL cholesterol in adults residing in African countries. We excluded reports on Africans living outside Africa, studies of individuals selected on the basis of existing dyslipidaemia or those including children and adolescents, and case series with a small sample size. The most frequently used cutoffs in the included studies were chosen for the subgroup analysis. We used random-effect model meta-analysis to derive the pooled prevalence of elevated total cholesterol, low HDL cholesterol, elevated LDL cholesterol, and elevated triglyceride concentrations. This study is registered with PROSPERO, number CRD42014015376. Findings: 181 studies (309 207 participants) were included in the meta-analysis. The pooled prevalence of dyslipidaemia in the general population from population-based studies was 23·6% (95% CI 18·4-29·2) for elevated concentrations of total cholesterol with a cutoff of at least 5·2 mmol/L, 41·1% (33·0-49·4) for low concentrations of HDL cholesterol with a cutoff of less than 1·0 mmol/L, 25·7% (16·2-36·6) for elevated concentrations of LDL cholesterol with a cutoff of at least 3·3 mmol/L, and 16·5% (11·8-21·6) for elevated concentrations of triglycerides with a cutoff of at least 1·7 mmol/L. Interpretation: The prevalence of dyslipidaemia is high in the general adult population in Africa. Ongoing efforts to reduce cardiovascular diseases in Africa should integrate effective detection and treatment of dyslipidaemia. Funding: None.